PENGELOLAAN ARSIP PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN PONOROGO TAHUN 2020 - Nurrohmah, Wavy (JI@P, 2021)
Archive has a role as a memory center, a source of information as well as a monitoring tool that is indispensable in every organization. The research method used is descriptive qualitative. Data collection techniques using interviews and documentation. The sampling technique in this study used purposive sampling so that there is a key informant and four people as supporting informants. The data analysis technique used an interactive analysis model (Miles and Huberman). The results obtained conclusions, namely: 1) archive management has been implemented in accordance with existing procedures which include budget planning, activity program planning, and financial accountability. 2) The Library and Archives Service has been running well The coordination of activities both vertically and horizontally runs smoothly. Socialization about archiving is also routinely carried out both internally at the Library and Archives Service as well as to all OPDs in the Ponorogo District Government with the material presented covering the theme of archival governance. 3) Actuating has been routinely carried out at the Library and Archives Service. This can be seen from the directives that are routinely carried out by the leadership both in direct meetings with employees and daily briefings in the official whatsapp group. 4) Internal archives supervision is carried out by the district's internal archives supervision team, while external archives supervision is carried out once a year by the archives supervision team. from the Province.Keywords: Planning, Organizing, Actuating, Controlling